Tourism and international business: The theoretical approach and practical experiences - Jovičić Dobrica; Stojiljković Marko (Glasnik Srpskog Geografskog Društva, 2011)
The paper discusses the relationships between tourism and international business. The research is based upon combining various theoretical concepts, significant empirical experiences and own attitudes of the authors. The key conclusion of the paper is that, despite of the partial progress in understanding tourism businesses, the relationships between tourism and international business need additional stimulus. In other words, more complete research in the related domains is needed in future. Any understanding of tourism is inadequate without appreciating the contributions that international business might bring, yet at the same time international business is incomplete in its coverage of international trade unless tourism is considered. The consumption-driven agenda of much tourism research has been favoured over supply-side discourses of the production process it self. That is why the role of major transnational companies, setting the trends that other types of firms in the tourism sector follow is focused in the paper.